Strengthening the Jombang AR Foundation as a New Foundation for Successor to the Old Foundation After the Foundation Law Regime - Mohammad Isrok; Radhityas Kharisma Nuryasinta (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
After the issuance of the Foundation Law, every Foundation that existed before the Foundation Law was required to adjust its Articles of Association with the provisions of the Foundation Law. If not, there will be legal implications for the Foundation, or in other words, the Foundation is legally weak which will also have an impact on the assets/wealth of the Foundation. Moving on from the results of observations, the service team found problems with the asset status/wealth of the Foundation caused by the less than optimal management of assets which must refer to the Waqf Law. Such problems place the position of the "AR" Foundation legally weak. This community service activity is intended to strengthen the partner's position as a new foundation, a continuation of the old foundation that has existed since 1977. The method used in this community service activity is the method of counseling and legal assistance directly to partners. The application of flowcharts, preparation of letters according to format, and tables of completeness of documents are the outputs of service activities for partners who can provide information and understanding about efforts to strengthen the Foundation.